Terpenoids and Their Biological Activities from Cinnamomum: A Review - Meiting Wu; Lin Ni; Haixiao Lu; Huiyou Xu; Shuangquan Zou; Xiaoxing Zou (Journal of Chemistry)
Cinnamomum is a genus of the family Lauraceae, which has been recognized worldwide as an important genus due to its beneficial uses. A great deal of research on its phytochemistry and pharmacological effects has been conducted. It is noteworthy that terpenoids are the characteristic of Cinnamomum due to the peculiar structures and significant biological effects. For a more in-depth study and the better use of Cinnamomum plants in the future, the chemical structures and biological effects of terpenoids obtained from Cinnamomum were summarized in the present study. To date, a total of 181 terpenoids with various skeletons have been isolated from Cinnamomum. These compounds have been demonstrated to play an important role in immunomodulatory, anti-inflammatory, antimicrobial, antioxidant, and anticancer activities. However, studies on the bioactive components from Cinnamomum plants have only focused on a dozen species. Hence, further studies on the potential pharmacological effects need to be conducted in the future.